Energy Dispersive X-ray Fluorescence Spectrometry and Kinetic Modeling of Elemental Strontium in Human Bone - Moise, Helen (My University, 2014)
For the first time in the available literature, this work presents data based on long term in-vivo human bone strontium measurements performed with an in-house custom developed I-125 based X-ray fluorescence system (IVXRF). Its negligible radiation risk and non-invasive nature allowed for frequent measurements at the ankle and finger sites, obtaining information about trabecular and cortical bone, respectively. While the phantom standards used to calibrate the system cannot be used to extract absolute bone strontium concentration, analysis of phantom consistency indicated excellent reproducibility, reporting a mean normalized strontium signal ± SD of 1.1198 ± 0.02171. This work comprises two important contributions besides system analysis; (i) the continued measurements of osteoporotic individuals self-administering with strontium supplements in order to acquire long term data and (ii) kinetic modeling. A total of 21 individuals (18 females, 3 males) were measured throughout the study, 10 are baseline individuals (no prior history of strontium intake and for whom natural bone strontium readings were acquired). Although similar patterns of strontium uptake were observed for all individuals, a wide variation of the strontium signal between individuals was observed, raising the question of physiological influences. Power and exponential functions were tested on 8 baseline individuals based on one and two compartmental configurations. Parameters represented the mean baseline strontium signal, half-life and strontium uptake. Ankle and finger values showed correlation of 0.804, which is significant at the 95% level. Half-lives (300 ± 163) days and (2200 ± 1661) days (p=0.000711 and p=0.0147) for the ankle and finger, respectively, indicated statistically significant different times, suggesting one compartment has a quicker turnover than the other. However, while the exponential model best describes the data set, the models were inconclusive which points to the need for a more controlled study, eliminating variable factors between individuals such as dosage, health and dietary consumption.